Occult constrictive pericardial disease emerging 40 years after chest radiation therapy: a case report - Chiaki Goten (BMC Cardiovascular Disorders, 2018)
Abstract Background The main etiology of constrictive pericarditis (CP) has changed from tuberculosis to therapeutic mediastinal radiation and cardiac surgery. Occult constrictive pericardial disease (OCPD) is a covert disease in which CP is manifested in a condition of volume overload. Case presentation A 60-year-old patient with a history of thoracic radiation therapy for non-Hodgkin’s lymphoma (40 years earlier) was transferred to our hospital for treatment of repeated congestive heart failure. For a preoperative hemodynamic study, pre-hydration with intravenous normal saline (50 mL/hour) was used to manifest the pericardial disease and prevent contrast-induced nephropathy. The hemodynamic study showed a right ventricular dip-plateau pattern and discordance of right and left ventricular systolic pressures during inspiration, which was not seen in the volume-controlled state. These responses were concordant with OCPD. A pericardiectomy, aortic valve replacement, and mitral and tricuspid valve repair were performed. Postoperatively, the heart failure was controlled with standard medication. Conclusions This case revealed a volume-induced change in hemodynamics in OCPD with severe combined valvular heart disease, which suggests the importance of considering OCPD in patients who had undergone radiation therapy 40 years before.